Anvendt forskning i umulige professioner - Hansen, Brian Benjamin (Tidsskrift for Professionsstudier, 2020)
The article raises some central questions regarding applied research by focusing on Sigmund Freud’s concept of “impossible professions”, e.g. educating, healing, and governing. It contributes with a discussion of the impasses and impossibilities of working professionally with subjects, not objects. To work with subjects requires not only (applied and effective) knowledge, but also the willingness to confront human actions and vicissitudes outside the framework of knowledge, as well as the disposition of the professional to give latitude to the subject. The article argues for these points through the lens of Freudian-Lacanian psychoanalytic approaches. The overall project of the text is to argue for the expediency of the concept of the impossible in understanding and researching professional practice.